Machiavellian, Equity Sensitivity, and Law Enforcement on the Perception of Tax Evasion Ethics - Dian Sulistyorini Wulandari; Edi Tri Wibowo; Perdana Ricardo (East Asian Journal of Multidisciplinary Research, 2023)
This study aims to examine the effect of Machiavellian, Equity Sensitivity, and Law Enforcement on the Ethical Perception of Tax Evasion with a case study at KPP Pratama Cibitung. This research uses a quantitative approach. The analysis used is Multiple Linear Regression Analysis with t-test, f-test, and coefficient of determination. The test instrument used in this study was SPSS Version 25. The test results in this study were the Machiavellian variable had a positive and significant effect on perceptions of tax evasion ethics, while equity sensitivity and law enforcement variables had a negative and significant effect on perceptions of tax evasion ethics. The coefficient of determination is 0.309 or 30.9%, which means that the magnitude of the influence of Machiavellian, equity sensitivity, and law enforcement on the ethical perception of tax evasion is 30.9% and the remaining 69.1% is explained by other factors. which were not described and tested in this study.